(untitled) (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2023)
Data is essential in decision-making, so it is important that citizens understand the value of open data. With the aim of innovating and promoting the use of open data, the artistic-technological project "Falla Inmaterial" is presented, with which scientific dissemination is carried out through massive festivals such as Las Fallas. This is an initiative aligned with citizen science that goes beyond the Fallas festivities and is conceived as a gamification tool with which to show social applications of engineering and data science.